Box - Behnken design to optimize the performance of a peak photovoltaic solar system - Delzo Salomé, Armando Siles (2021)
The objective of the research was to design a Box Behnken system to optimize the performance of a peak photovoltaic solar system in the Mantaro Valley under conditions of high population density. For this, the system was located in a zone of moderate urban density in the city of Huancayo, Junín region, in the central region of Peru with coordinates 12 ° 03'29.0 "S 75 ° 13'12.9" W. Measurements were made in the regional summer season. The variables evaluated for optimization in the Behnken Box Design were: orientation, angle of inclination of the solar panel and time of exposure. Behavior was modeled using the response surface for single and combined variables, comparing the variation in the potential difference (V). The results showed that the variable of greatest significance for the potential variation was the angle of inclination, with a standardized effect of 3.48 and 95% significance. All the residuals of the factorial diagram were found within +0.8 and -0.8, indicating that the experimental procedure applying the Box Behnken method did not present outliers. It was concluded that it is possible to maximize the potential difference of a solar collection system in the Mantaro Valley, in an area of ​​high urban density, prioritizing the angle of incidence of radiation.